Orlov til børnepasning - en familiepolitisk revolution - Olsen, Bente Marianne (Kvinder, Køn & Forskning, 1997)
Does Danish legislation concerning child care leave for parents promote equality among men and women in parenting? The special legislation from 1994 has so far had no appeal to fathers. In addition the law seems to weaken the commitment to the labour market especially among unemployed and most of them women. So in reality the law which has been launched as a "revolution of family policy" has furthered the marginalization of women on the labour market. A new proposal aiming at more equality among parents is set forth. The proposal includes a leave of eight weeks for fathers, in continuation of current maternity and parental leave, with full compensation for lost income. It is argued that the periods of leave ought to include the rights to seniority and pension.